2017
DOI: 10.1007/s10068-017-0246-4
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antimicrobial activities of fresh garlic and aged garlic by-products extracted with different solvents

Abstract: This study aims to investigate antioxidative and antibacterial properties of fresh garlic (non-aged, NG) and aged garlic (AG) by-products extracted with distilled water, ethanol, or chloroform. To determine their antioxidative and antibacterial capacities, 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay, 2,2'-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS) radical scavenging assay, and HO radical scavenging activity, Fe chelating activity, total ferric reducing antioxidant power (FRAP), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
92
5
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(111 citation statements)
references
References 30 publications
8
92
5
6
Order By: Relevance
“…Pavlovic et al () studied different extracts (different rates of ethanol, water, and methanol) of wild garlic ( Allium ursinum ) and radical scavenging activities were 0.63–1.40 mg/ml IC 50 values. In the other study Jang et al (), DPPH radical scavenging activity results of water and ethanol extracts of garlic ( Allium sativum ) were 20.86 ± 0.29 and 11.22 ± 0.14, respectively.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Pavlovic et al () studied different extracts (different rates of ethanol, water, and methanol) of wild garlic ( Allium ursinum ) and radical scavenging activities were 0.63–1.40 mg/ml IC 50 values. In the other study Jang et al (), DPPH radical scavenging activity results of water and ethanol extracts of garlic ( Allium sativum ) were 20.86 ± 0.29 and 11.22 ± 0.14, respectively.…”
Section: Resultsmentioning
confidence: 87%
“…In our study bulb ethanol extract of A. macrochaetum showed the best activity among the tested extracts with IC 50 : 55.90 ± 1.08 µg/ml value (Table ). In the study Jang et al (), ABTS cation radical scavenging activity results of water and ethanol extracts of garlic ( Allium sativum ) were 35.92 ± 0.43 and 19.78 ± 0.15 µg/ml, respectively. The study of Alagarsamy et al (), ABTS radical scavenging activities of aqueous and ethanolic extracts of the Allium oschaninii were determined as IC 50 values 0.2524 and 0.5467 mg/ml, respectively.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, garlic extract was found to increase the activities of some antioxidant enzymes (e.g., superoxide dismutase (SOD)) and decrease glutathione peroxidase (GSH-Px) in hepatic tissues of rats. Notably, several reports indicated that AGE rich in flavonoid, phenol, and different sulfur compounds e.g., SAC shows high radical scavenging activity [65]. Additionally, AGE acted by stimulating the expression of different antioxidant enzymes, namely glutamate-cysteine ligase modifier (GCLM) and heme oxygenase-1 (HO-1) subunit by the nuclear factor erythrobia-2 related factor 2 (Nrf2)-antioxidant response element (ARE) pathway that is responsible for human endothelial cells protection against oxidative stress [66].…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Some literature exclude oxygen from the chalcogenides discussion as oxygen appears in almost all materials [3]. Oxygen and sulfur are contained in so many secondary metabolites in living things and also in bigger molecules in tissue [6,18,[31][32][33][34]. The process of changing compounds during food treatment enables one to establish new natural resources for modern herbal medicine for cancerous treatment [7,[35][36][37][38][39].…”
Section: Nature Of Chalcogen Compounds and Chalcogen Materialsmentioning
confidence: 99%